THE IMPLEMENTATION OF CHAIN DRILL IN TEACHING SPEAKING OF RECOUNT TEXT TO THE EIGHT GRADERS OF JUNIOR HIGH SCHOOL (RETAIN, 2017)
THE IMPLEMENTATION OF CHAIN DRILL IN TEACHING SPEAKING OF RECOUNT TEXT TO THE EIGHT GRADERS OF JUNIOR HIGH SCHOOL Reta Maya Saprima English Education Department, Faculty of Languages and Arts, State University of Surabaya retasaprima@gmail.com Abstrak Penelitian ini bertujuan untuk mendeskripsikan pelaksanaan latihan berantai dalam pengajaran berbicara menggunakan teks recount. Teknik pelatihan berantai adalah teknik yang efektif yang terdapat dalam Audio Lingual Method yang telah menjadi teknik yang menarik. Penelitian ini menggunakan Desain Kualitatif dengan 38 siswa sebagai peserta. Peneliti juga menggunakan kelas aktif dalam melakukan penelitian. Instrumen penelitian yang digunakan dalam penelitin kali ini adalah catatan lapangan, rekaman kegiatan berbicara siswa, wawancara dan rubrik berbicara. Dalam menganalisa data, peneliti mengubah rekaman pembicaraan menjadi transkripsi. Kemudian, menganalisis data dengan rubrik berbicara. Hasilnya menunjukkan bahwa guru yang menerapkan latihan berantai dalam mengajar berbicara bahasa Inggris secara alami dan lancar. Singkatnya, para siswa termotivasi dalam berbicara bahasa Inggris dan membantu mereka memahami teks dengan situasi yang menyenangkan. Kata Kunci: latihan berantai, berbicara Bahasa Inggris, teks recount Abstract This study aims to describe the implementation of chain drill in teaching speaking of recount text. Chain drill technique is an effective technique from Audio Lingual Method that has been an interesting technique. This research used Qualitative Design with 38 students as the participants. The researcher also used an active class in conducting the research. The research instruments were field notes, students’ speaking recording, interview and speaking rubric. In analyzing the data, the researcher turns the speaking recording into transcription. Then, analyze the data with speaking rubric. The result showed that the teacher who implements chain drill in teaching speaking English can make the students are able to speak English naturally and fluency. In short, the students were motivate in learning speaking English and help them easier to comprehend the text with fun situation. Keywords: chain drill, speaking English, recount text